Mathematics
Manjarres679
37

(07.05 MC) An equation is shown below: 4x + 2(x – 3) = 4x + 2x – 11 Part A: Solve the equation and write the number of solutions. Show all the steps. (6 points) Part B: Name one property you used to solve this equation. (4 points

+3
(2) Answers
alex9944

There are no solutions idk what it means by property, I just solved it by distributing the 2 then subtracting 6x on both sides which left -6=-11 which do not equal so yea 

latinaberryhill

4x + 2(x - 3) = 4x + 2x - 11 4x + 2x - 6 = 4x + 2x - 11 6x - 6 = 6x - 11 6x - 6x = -11 + 6 0 = -5...incorrect......this has no solution...0 solutions one property used was the distributive property :2(x - 3) = 2x - 6

Add answer